Our beloved polites : studies presented to P.J. Rhodes - Rhodes, P. J.; Leão, Delfim Ferreira; Ferreira, Daniela; Rodrigues, Nuno Simões; Morais, Rui (Archaeopress Archaeology, 2022)
28 contributions pay tribute to one of the most remarkable historians of ancient Greece, Professor P.J. Rhodes, to celebrate his life and work which has been and will continue to be a major reference for scholars around the world. The volume is organised in four sections - history and biography, law, politics, and epigraphy.